Renal angiomyolipoma-investigating radiological signs indicative of risk for bleeding - Jesper Swärd; Karl Bohlin; Olof Henrikson; Sven Lundstam; Ralph Peeker; Anna Grenabo Bergdahl (Insights into Imaging)
Abstract Objectives To compare imaging differences between bleeding and non-bleeding angiomyolipoma with respect to the proportion and attenuation of the angiomyogenic component and the occurrence and size of aneurysms. Materials and methods CT scans and angiographies preceding 58 consecutive embolisations at two institutions from 1999 to 2018 were analysed retrospectively. Tumour volume was measured by contouring the angiomyolipoma on CT scans. The partial volume of the angiomyogenic component (blood vessels and smooth muscle relative to fatty tissue) was derived using attenuation threshold values measured in Hounsfield Units. Results Bleeding angiomyolipoma exhibited a significantly higher proportion of angiomyogenic component (23%) than non-bleeding angiomyolipoma (8%) (p = 0.042). Angiomyolipoma with 0–5% angiomyogenic component had a lower risk of bleeding compared to those with ≥ 5% angiomyogenic component (13% vs 42%). Mean attenuation values of angiomyogenic components did not differ between bleeders and non-bleeders. Aneurysms were observed in 24% of angiomyolipoma during angiography. No statistically significant association was found between the occurrence of aneurysms and bleeding, neither when all aneurysms were included nor when only aneurysms ≥ 5 mm were considered. Tuberous sclerosis patients had larger tumours (11.4 cm vs 6.0 cm), but no significant difference in bleeding was observed (p = 0.53). Conclusions A higher proportion of the angiomyogenic component in bleeding renal angiomyolipoma suggests a possible association with bleeding. Angiomyolipoma with less than 5% angiomyogenic components may represent a subgroup with a reduced risk of bleeding. Our findings do not confirm the widely accepted assumption that aneurysms significantly increase the risk of bleeding. Critical relevance statement Measuring the angiomyogenic component in renal angiomyolipoma could help address current knowledge gaps and aid in the more efficient selection of patients for therapeutic interventions. Key Points Identifying risk factors for bleeding beyond tumour size is important. Very low angiomyogenic component tumours may have reduced bleeding risk. The presence of aneurysms may not significantly increase bleeding risk. Reporting angiomyogenic proportion on CT may aid in treatment decisions. Graphical Abstract